BUILDING, CODIFYING AND APPLYING THE MEASURE OF EMOTIONAL AROUSAL AMONG PREMIER LEAGUE HANDBALL PLAYERS - Assistant Lecturer.Hassanein Sharif AbdelWahab (American Journals, 2023)
The importance of the research comes in the need of handball players to improve the rates of emotional arousal that they are exposed to during training or competitions, as the players' ability to emotional arousal will be coupled with the upgrading of the level of players for their skillful performance and the development of their athletic level up to the higher levels, and the research problem stands out In the fact that the player’s control over managing his emotions, presenting them, and showing them in the best way, it will facilitate the player’s thinking process and orientation towards the goal in light of the conditions of critical sports competition, as well as moderating the rates of emotional arousal that will lead to the occurrence of emotional balance for the players, and the lack of measures that measure the management of emotions in the sports field, which prompted the researcher to build a measure of emotional arousal and ration it according to the models of sudden sharp regression and reflexive transformation, and to know the dimensions of the measure of emotional arousal according to the models of sudden sharp regression and reflexive transformation. The researcher used the descriptive survey method for the purpose of building a measure of emotional arousal for Premier League players in handball, and the measure was applied in its final form to a sample of (30) players from Iraqi handball clubs, then the statistical transactions were conducted to extract indicators of honesty, stability and objectivity, and then to determine the standard levels for the two measures. The researcher used the statistical package (SPSS)) to obtain the results of the study for analysis and discussion in the fourth chapter, so that the researcher reached a set of conclusions, including: The emotional arousal scale was built and codified with (36) paragraphs distributed on two axes, and special grades were set for the Premier League players tomorrow. Hand. The handball players were distinguished by medium degrees in emotional arousal and its two axes (sudden sharp decline) and (reflexive transformation). The emergence of Statistically significant differences between the hypothetical mean and the arithmetic median on the vigilance scale in favor of arithmetic mean of the sample, and that is what it possesses of the ability to manage emotions and their characterization of moderate arousal.
Keywords: Emotional arousal, Premier League, handball, the players, analytical thinking.